Synthesis and Reactions of Some 4'-(2-Pentachlorophenxoyethoxy) Substituted Chalcones - Sukhwal, S.; Ashawa, A.; Verma, B.L. (Asian Journal of Chemistry, 2012)
Reaction of pentachlorophenol with 1,2-dibromoethane gave a mixture of 2-(Pentachlorophenoxy)-ethylbromide(III) and 1,2-bis-(Pentachlorophenoxy)-ethane (IV) which were separated as aceton soluble (III) and insoluble (IV) components. Reaction of (III) with p-hydroxyacetophenone (Va) and resacetophenone (Vb) resulted 4-(2-pentachlorophenoxy ethoxy)-acetophenone (VIa) and 2-hydroxy-4-(2-pentacholorophenoxy ethoxy)-acetophenone (VIb) respectively. Condensation of VIa and VIb with p-substituted aromatic aldehydes (VII) affored the corresponding chalcones (VIII). Compounds (VIIIb) was treated with DMSO and iodine, bromine in acetic acid and alkaline hydrogen peroxide to afford flavone (IXa), dibromochalcone (X) and flavonol (IXb) derivatives. The structures of the synthesised compounds have been established on the basis of elemental analysis and spectral data. Some of the synthesised compounds were found to be active against number of micro-organisms.